Case Report: About a Case of Hyperammonemia Syndrome Following Lung Transplantation: Could Metagenomic Next-Generation Sequencing Improve the Clinical Management? - Michel, Charlotte; Raimo, Michela; Lazarevic, Vladimir; Gaïa, Nadia; Leduc, Nina; Knoop, Christiane; Hallin, Marie; Vandenberg, Olivier; Schrenzel, Jacques; Grimaldi, David; Hites, Maya (Frontiers in Medicine, 2021)
Background: Mycoplasma hominis and Ureaplasma sp. are responsible for opportunistic infections in transplant patients, sometimes causing a life-threatening hyperammonemia syndrome. Both pathogens are not identified with standard microbiology techniques, resulting in missed or delayed diagnosis. We present a clinical case that illustrates the added value that Next Generation Sequencing (NGS) may offer in the diagnosis of respiratory infections in immune-compromised patients. Results: A 55 years-old man with idiopathic pulmonary fibrosis underwent double lung transplantation. He received antibiotic prophylaxis with piperacillin-tazobactam and azythromycin. At day 4 post-transplantation (PTx), the patient presented an acute respiratory distress. A broncho-alveolar lavage (BAL) was performed. At day 5 PTx, the patient presented a status epilepticus due to diffuse cerebral oedema. Serum ammonia concentration was 661 µmol/dL. BAL bacterial culture was negative. Because of the clinical presentation, special cultures were performed and identified 100.000 CFU/mL of M. hominis and Ureaplasma sp. and specific PCRs were positive for M. hominis and U. parvum. Antibiotic therapy was shifted to therapeutic dose of azithromycin and doxycycline; within 48h ammonia serum concentrations returned to normal but the coma persisted several weeks, followed by a persistent frontal lobe syndrome. A follow-up BAL was performed on day 11 Ptx. The Mycoplasma/Ureaplasma culture was negative, yet the specific PCRs remained positive. Bacterial culture found 100 CFU/ml of Staphylococcus aureus and viral culture was positive for Herpes Simplex Virus-1. These results were confirmed by metagenomic next-generation sequencing (mNGS). In the bacterial fraction, the majority of reads belonged to Corynebacterium propinquum (34.7%), S. aureus (24.1%) and Staphylococcus epidermidis (17.1%). Reads assigned to M. hominis, Ureaplasma urealyticum and parvum represented 0.71%, 0.13% and 0.04% of the bacterial fraction and corresponded to 6.9103, 9.7102 and 3.7102 genome equivalents per mL of BAL fluid, respectively. These results are in favor of a cure of the atypical infection. Conclusions: mNGS offered added diagnostic and quantitative values compared to classic PCRs which can remain positive after resolved infections. The initiation of appropriate antibiotic therapy would have occurred earlier on, possibly resulting in a better clinical outcome if mNGS had been performed in a routine fashion.